Glacier recession in the Altai Mountains of Mongolia in 1990–2016. Issue 2 (3rd April 2018) - Pan, Caleb G.; Pope, Allen; Kamp, Ulrich; Dashtseren, Avirmed; Walther, Michael; Syromyatina, Margarita V.
ABSTRACT: Relatively little is known about glaciers in the continental climates of North Asia and even less is known about the glaciers of the Mongolian Altai. In an attempt to fill this knowledge gap, we present a new satellite-derived glacier inventory for the Altai Mountains of Mongolia, using the recently launched Landat-8 OLI and Sentinel-2A MSI sensors to monitor glacier change from 1990 to 2016. We examine changes in climatic trends and glacier topomorphological parameters in conjunction with glacier fluctuations to determine governing controls over glacier recession in the Altai Mountains. Our glacier mapping results produced 627 debris-free glaciers with an area of 334.0 ± 42.3 km 2 as of 2016. These data were made available for download through the Global Land Ice Measurements from Space (GLIMS) initiative. A subsample of 206 glaciers that were mapped in 1990, 2000, 2010, and 2016 revealed that from 1990 to 2016, glacier area reduced by 43% at 6.4 ± 0.4 km 2 yr −1 . Glacier recession was greatest from 1990 to 2000 at a rate of 10.9 ± 0.8 km 2 yr −1, followed by 2010–2016 at 4.4 ± 0.3 km 2 yr −1 . Rates of glacier recession were significantly correlated with intrinsic glacier parameters, including mean, minimum and range elevations, mean slope and aspect. Furthermore, climate records indicated the warmest summer temperatures occurred during periods of high glacier recession.